2016
DOI: 10.24831/jai.v44i1.12508
|View full text |Cite
|
Sign up to set email alerts
|

Karakter Morfologi dan Potensi Produksi Beberapa Aksesi Sagu (Metroxylon spp.) di Kabupaten Sorong Selatan, Papua Barat

Abstract: ABSTRACT<br /><br />Sago palm is a carbohydrate source which has the highest carbohydrate content compared to the other crops. It can produce about 200-400 kg per trunk of sago dry starch. More than 50% sago palm population in the world are grown in Indonesia and 90% sago palm in Indonesia is found in Papua. This research was aimed to characterize several sago palm accessions in South Sorong District, West Papua. There were 12 accessions observed, i.e. Fasai, Fasampe, Falia, Fanomik, Fasongka, Fafi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 4 publications
0
9
0
10
Order By: Relevance
“…Bujang (2008) reported that the yield potential of sago palm in Malaysia is reached 25 tons of starch ha -1 year -1 . The dried starch produced by sago palm was reported between 200-400 kg tree -1 (Dewi et al 2016). Sago palm encountered in Sentani, Papua, Indonesia with local names Para, Panne, Yebha, Wanny sequentially have average production capability of 674 kg, 576 kg, 512 kg, 491 kg tree -1 (Yamamoto 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Bujang (2008) reported that the yield potential of sago palm in Malaysia is reached 25 tons of starch ha -1 year -1 . The dried starch produced by sago palm was reported between 200-400 kg tree -1 (Dewi et al 2016). Sago palm encountered in Sentani, Papua, Indonesia with local names Para, Panne, Yebha, Wanny sequentially have average production capability of 674 kg, 576 kg, 512 kg, 491 kg tree -1 (Yamamoto 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Tanaman sawi merupakan salah satu Sagu merupakan tanaman sumber bahan pangan yang memiliki manfaat cukup besar. Adawiyah and Dirgantoro (2019); Dewi, Bintoro, and Sudradjat (2016) menyatakan bahwa sagu merupakan tanaman penghasil karbohidrat yang tinggi dan bersumber dari batang. Ahmad, Bintoro, and Supijatno (2016); Bintoro, Purwanto, and Amarilis (2010) menyatakan bahwa tanaman sagu memiliki pati yang tinggi yang dapat mencapai 200 sampai 800 kg pati kering per pohon.…”
Section: Pendahuluanunclassified
“…Pemanfaatan ampas sagu sebagai alternatif pakan ternak dapat dilakukan di Papua. Hal ini karena Papua mempunyai kawasan lahan sagu terbesar di Indonesia dengan tingat produksi tinggi (Dewi et al, 2016). Menurut Pamungkas (2011) dan Fitrihidajati et al (2015) bahan alternatif pakan dapat ditingkatkan kualitasnya dengan cara dilakukan fermentasi.…”
Section: Pengaruh Pakan Fermentasi Ampas Sagu (Fas) Terhadap Bobot Ayam Kampungunclassified